Profitability of Romanian companies on food trade - Cristian George Popescu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Through this paper we intend to highlight some answers of the questions that we ask ourselves often be in terms of the entrepreneur who wants to develop a business with some ideas on food trade, either in terms of consumer who knows sometimes the prices of some products are more expensive than other similar food stores. Here are some of the questions that we seek answers in the paper: How profitable are companies operating in the food trade, regardless of their organizational structure? What is the threshold of affordability of food trading enterprises on running a business? What is the contribution to the state budget of an undertaking of this kind and under the laws of Romania as moral are these fees compared to exertion by business to support a business? What would be the daily earnings of a company to survive the current economic circumstances? What major challenges facing NGOs engaged in charitable activities to help disadvantaged groups such as state aid and the legal entity? (some NGOs even assuming important functions that should be the government rule).
Keywords: 330; financial results; market food; food trade; profitability; NGO